The influence of the French language on the names of the Bulgarian and Turkish media - Vesselinov, D.; Yordanova, M. (KU Publ., 2022)
The article is devoted to the study of the influence of the French language on the names of the Bulgarian and Turkish media. The empruntological analysis of the French influence on the formation of Bulgarian and Turkish terms for naming newspapers and magazines shows a complex process of designing the French experience in the print media on the Bulgarian and Turkish language systems. The aim of the study is to trace the process of penetration of French terms for print media (gazette, journal, revue) and their derivatives (gazetier, journaliste; journalisme; journalistique) in Turkish and Bulgarian. The scope of the research is limited to a thematic field composed of the French for the main print media (gazette, journal, revue) with the respective empruntological projections in Turkish and Bulgarian (receiving languages). It is of interest to trace the semantic changes of these Frenchisms in the respective linguistic and cultural neighboring spaces.
Болгар және түрік тілдеріндегі БАҚ атауларына француз тілінің әсері
Влияние французского языка на названия болгарских и турецких средств массовой информации
Keywords: media; empruntology; journal; revue; gazette; Turkish language; borrowings; Bulgarian language; French language